2017
DOI: 10.1037/cns0000115
|View full text |Cite
|
Sign up to set email alerts
|

The dynamical signature of conscious processing: From modality-specific percepts to complex episodes.

Abstract: The search for neural correlates of human consciousness in past decades has been based on different assumptions and methods. Some researchers assume that conscious functions are localized in brain circuits, and ultimately pinned down to single neuron selective firing at the millisecond range, while others search for dynamic patterns, as the synchrony of neural potentials or slow waves in brain tissue. We raise and review evidence for the hypothesis that the composition of conscious processes has a dual dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 98 publications
1
7
0
Order By: Relevance
“…Measurement of the duration of these recorded texts revealed a mean duration around 2000 ms. Because of this, the display of the written texts were fixed in 2500ms. Taking these facts into account, Rocha et al (2015) and Pereira et al (2017) interpreted the similarity of ) ( _ s v T calculated for EEG epochs Q and S as due to a modular cortical processing of 2000 ms composed by 4 main steps disclosed by the identified W i s. Similar modular cortical processing was observed for other types of reasoning studied in our group , too…”
Section: -Era Wavessupporting
confidence: 73%
See 1 more Smart Citation
“…Measurement of the duration of these recorded texts revealed a mean duration around 2000 ms. Because of this, the display of the written texts were fixed in 2500ms. Taking these facts into account, Rocha et al (2015) and Pereira et al (2017) interpreted the similarity of ) ( _ s v T calculated for EEG epochs Q and S as due to a modular cortical processing of 2000 ms composed by 4 main steps disclosed by the identified W i s. Similar modular cortical processing was observed for other types of reasoning studied in our group , too…”
Section: -Era Wavessupporting
confidence: 73%
“…In this context, speech onset triggers cycles of neuronal encoding at embedded syllabic, phonemic and phrasal scales and speech decoding becomes a process controlled by a time-varying, hierarchical window structure synchronized with the input (Ghitza, 2011). Ghitza (2013) Rocha et al (Pereira Jr, Foz, and Rocha, 2017;Rocha et al, 2015Rocha et al, , 2017 identified a modular ERA segmentation in many distinct cognitive tasks and, because of this, they proposed reasoning to be supported by a set of modular cycles of message exchange between local and distant sets of neurons, organized by a complex cyclic multimodal oscillatory synchronized brain activity. Here, this modular oscillatory activity was detailed and its possible cortical sources identified.…”
Section: Resultsmentioning
confidence: 99%
“…Following advances in the study of glial cells (Tadi et al, 2015; Dallérac and Rouach, 2016; Papouin et al, 2017), the possible relation of these synchronizations with consciousness could be found in the interaction between neurons and astrocytes. According to the “astrocentric hypothesis” (Robertson, 2013), conscious perception arises through a process of global synchrony in which information patterns carried by neuronal spike trains are transferred to astrocytic waves (Pereira and Furlan, 2009; Pereira et al, 2017). It is suggested that the persistent traces revealed in our simulation are at the roots of this transfer process.…”
Section: Resultsmentioning
confidence: 99%
“…Spike trains encode information by means of frequency and phase in populations of axons. The CNS constructs episodes from the ensemble of neuron firing patterns received within a temporal period of approximately 2 to 3 s [26]. The concepts of feature-detectors and population-rate coding can be combined in the idea of a sparse population code [27].…”
Section: Glutamate and Calcium Mechanisms In The Control Of Basal Homeostasismentioning
confidence: 99%